Spiritual Tourism – A Literature Review to Encourage Reflection on Emerging Concerns - Soares, Natacha (2024)
T he potential of tourism to provide opportunities for people to explore their spirituality is increasingly recognized. In this article, we intend to review the existing empirical literature on spiritual tourism demand, systematizing some key elements to consider in the future development of this kind of tourism and emphasizing the potential contribution of this type of tourism towards sustainability. Research from the Scopus database was conducted to accomplish this objective, analyzing 21 full empirical articles. A qualitative methodology was adopted. From the analysis of the main results, research paths can be identified for the future, and the dimensions/ themes most frequently included in the existing research can be highlighted, such as the profile of spiritual tourists, the most frequent motivations and the key features of spiritual destinations. T he study ends by reflecting on sustainability issues that appear vital to consider in future studies and/or new offers, as well as recognizing the need to address the negative issues most linked to spiritual tourism, such as the use of drugs.